2017
DOI: 10.1038/s41598-017-17213-4
|View full text |Cite
|
Sign up to set email alerts
|

Robust method for identification of prognostic gene signatures from gene expression profiles

Abstract: In the last decade, many attempts have been made to use gene expression profiles to identify prognostic genes for various types of cancer. Previous studies evaluating the prognostic value of genes suffered by failing to solve the critical problem of classifying patients into different risk groups based on specific gene expression threshold levels. Here, we present a novel method, called iterative patient partitioning (IPP), which was inspired by the receiver operating characteristic (ROC) curve, is based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The integrin receptor family consists of 18 α subunits and 8 β subunits that assemble as non-covalently connected heterodimers and organized into 24 different ITGs 7 . Our current in silico study and another previous report suggest that ITGα3 plays a significant role in adverse prognosis of pancreatic cancer 8,9 . However, the underlying mechanism is poorly understood.…”
Section: Introductionsupporting
confidence: 69%
“…The integrin receptor family consists of 18 α subunits and 8 β subunits that assemble as non-covalently connected heterodimers and organized into 24 different ITGs 7 . Our current in silico study and another previous report suggest that ITGα3 plays a significant role in adverse prognosis of pancreatic cancer 8,9 . However, the underlying mechanism is poorly understood.…”
Section: Introductionsupporting
confidence: 69%
“…Researchers recently reported two prognostic gene signatures constructed using DCBLD2 in PDAC ( Raman et al, 2018 ; Feng et al, 2020 ). The prognostic accuracy of DCBLD2 was certainly inferior to that of gene models, because accumulating evidence had demonstrated that multi-gene signatures achieved higher prognostic accuracy compared with a single gene ( Beane et al, 2009 ; Sim et al, 2017 ; Schmidt et al, 2018 ; Huang et al, 2020 ; Ahluwalia et al, 2021 ). However, we found that the diagnostic accuracy of DCBLD2 was close to or no less than that of gene models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to optimizing the parametric space and modeling assumptions for better results, tests could be employed to analyze the performance of the pipeline on a variety of gene sets to better inform the interpretation of differential expression of the gene set of interest (GTs). Robustness testing could be employed to investigate the quality of the results from independent datasets (Sim et al 2017), for example, from a cancer dataset not provided by TCGA but of the same type. Permutation testing could be employed across randomly sampled subsets of data to define DEGs across permutations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new methods are constantly being developed to address issues related to the quality of differential expression analysis and improve the identification of DEGs. Recent methods have been proposed to overcome the issue of threshold decisions (Sim et al 2017), and to employ the knowledge of a gene’s prior probability of DE to better predict that gene’s differential expression across diverse biological experiments (Crow et al 2019).…”
Section: Discussionmentioning
confidence: 99%